2004
DOI: 10.1021/jm0407658
|View full text |Cite
|
Sign up to set email alerts
|

4-Benzyl- and 4-Benzoyl-3-dimethylaminopyridin-2(1H)-ones, a New Family of Potent Anti-HIV Agents:  Optimization and in Vitro Evaluation against Clinically Important HIV Mutant Strains

Abstract: The 4-benzyl and 4-benzoyl-3-dimethylaminopyridinones 13 and 14 are representatives of a new class of highly potent non nucleoside type inhibitors of HIV-1 reverse transcriptase. To conduct SAR studies on these two lead compounds, 102 new analogues were prepared. Thirty-three compounds displayed nanomolar range activity in vitro against wild-type HIV-1, and among these, 18 were active against the 103N, Y181C, and Y188L mutant strains with IC50 values inferior to 1 microM. Evaluation of this group of analogues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…Differences of potency between the E form (TMC278) and the Z form (compound 1) were in agreement with the docking studies, which showed stronger interactions of the cyano group in the E-orientation than in the Z-orientation with the W229 region in the binding site of the RT enzyme. Except for compound 3, substituents in the alpha or beta position on the cyanovinyl group [10,12,13] did not modify the potency against the wild-type single-and double-mutant strains. The introduction of a methylene group between the vinyl and the cyano group was detrimental to the activity.…”
Section: Discoverymentioning
confidence: 89%
See 1 more Smart Citation
“…Differences of potency between the E form (TMC278) and the Z form (compound 1) were in agreement with the docking studies, which showed stronger interactions of the cyano group in the E-orientation than in the Z-orientation with the W229 region in the binding site of the RT enzyme. Except for compound 3, substituents in the alpha or beta position on the cyanovinyl group [10,12,13] did not modify the potency against the wild-type single-and double-mutant strains. The introduction of a methylene group between the vinyl and the cyano group was detrimental to the activity.…”
Section: Discoverymentioning
confidence: 89%
“…The marked structural diversity that is displayed by these classes of compounds would suggest that there are still ample opportunities to discover new highly potent NNRTIs. Johnson & Johnson pharmaceutical research and development, in partnership with Institut-Curie (France), contributed to the discovery of the arylpyridone class, with 4-benzyl-3-dimethylamino-2-pyridone (R131459) as the first representative compound [12]. This compound, a hybrid of the Merck pyridone L-697,661 and HEPT derivative, is active at submicromolar concentrations against wild-type HIV-1 and maintains a good level of activity against NVPresistant HIV-1 strains.…”
Section: Discoverymentioning
confidence: 99%
“…[19] Pyridinone-HEPT hybrids Considering the partial structure similarity of Merck pyridinones and 1-[(2-hydroxyethoxy)methyl]-6-(phenylthio)thymine (HEPT) derivatives such as GCA-186 (Figure 2), a very extensive synthetic program was initiated leading to the development of a series of potent pyridinone-HEPT hybrids. Subtypes of these hybrids include 4-arylthiopyridin-2(1H)-ones, [20,21] 4-benzylpyridin-2(1H)-ones, [22][23][24] 4-aryloxypyridin-2(1H)-ones, [25,26] and 4-benzoylpyridin-2(1H)-ones. [23,24] 4-Benzylpyridin-2(1H)-ones were further coupled with the nucleoside RT inhibitor azidothymidine (AZT) to test a hypothesis of "mixture site" inhibitors.…”
Section: Discovery and Developmentmentioning
confidence: 99%
“…Subtypes of these hybrids include 4-arylthiopyridin-2(1H)-ones, [20,21] 4-benzylpyridin-2(1H)-ones, [22][23][24] 4-aryloxypyridin-2(1H)-ones, [25,26] and 4-benzoylpyridin-2(1H)-ones. [23,24] 4-Benzylpyridin-2(1H)-ones were further coupled with the nucleoside RT inhibitor azidothymidine (AZT) to test a hypothesis of "mixture site" inhibitors. However, the pyridinone-AZT conjugates were inactive.…”
Section: Discovery and Developmentmentioning
confidence: 99%
See 1 more Smart Citation